T2R bitter taste receptors regulate apoptosis and may be associated with survival in head and neck squamous cell carcinoma. Issue 7 (14th December 2021) - Carey, Ryan M.; McMahon, Derek B.; Miller, Zoey A.; Kim, TaeBeom; Rajasekaran, Karthik; Gopallawa, Indiwari; Newman, Jason G.; Basu, Devraj; Nead, Kevin T.; White, Elizabeth A.; Lee, Robert J.
Abstract : Better management of head and neck squamous cell carcinomas (HNSCCs) requires a clearer understanding of tumor biology and disease risk. Bitter taste receptors (T2Rs) have been studied in several cancers, including thyroid, salivary, and GI, but their role in HNSCC has not been explored. We found that HNSCC patient samples and cell lines expressed functional T2Rs on both the cell and nuclear membranes. Bitter compounds, including bacterial metabolites, activated T2R‐mediated nuclear Ca 2+ responses leading to mitochondrial depolarization, caspase activation, and ultimately apoptosis. Buffering nuclear Ca 2+ elevation blocked caspase activation. Furthermore, increased expression of T2Rs in HNSCCs from The Cancer Genome Atlas is associated with improved overall survival. This work suggests that T2Rs are potential biomarkers to predict outcomes and guide treatment selection, may be leveraged as therapeutic targets to stimulate tumor apoptosis, and may mediate tumor‐microbiome crosstalk in HNSCC. Abstract : Head and neck squamous cell carcinoma (HNSCC) cells express bitter taste receptors (T2Rs) on the cell and nuclear membranes. T2Rs are activated by various bitter compounds including secreted bacterial products, leading to nuclear calcium (Ca 2+ ) responses, caspase activation, mitochondrial depolarization, and apoptosis. HNSCC tumors that express higher levels of T2Rs are associated with improved overall survival. Created with BioRender.